2009
DOI: 10.1089/fpd.2008.0185
|View full text |Cite
|
Sign up to set email alerts
|

GenotypingCampylobacter jejuniby Comparative Genome Indexing: An Evaluation with Pulsed-Field Gel Electrophoresis andflaASVR Sequencing

Abstract: Comparative genome indexing (CGI) using whole-genome DNA microarrays was evaluated as a means of genotyping Campylobacter jejuni relative to two standard methods, pulsed-field gel electrophoresis (PFGE) and flaA short variable region sequencing (flaA SVR typing). Thirty-six geographically diverse C. jejuni isolates were selected from a collection of cattle and chicken isolates. The BioNumerics software program was used for cluster analysis of the data from all 36 isolates for each of the three typing methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The flagellin gene has been a well-accepted marker for Campylobacter genotyping for over 2 decades (4,16,18,19,22,25,32). In this study we have developed a genotyping method based on flaA interrogation using HRM analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The flagellin gene has been a well-accepted marker for Campylobacter genotyping for over 2 decades (4,16,18,19,22,25,32). In this study we have developed a genotyping method based on flaA interrogation using HRM analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these limitations, CGI has been important for investigating the genomic diversity of C. jejuni (Pearson et al, 2003;Taboada et al, 2004;Parker et al, 2006). As a genotyping tool, CGI provides isolatespecific information on a genome-wide scale (Leonard et al, 2003;Pittenger et al, 2009). But as Taboada et al (2004) note, the number of variable marker genes most valuable (i.e., informative) for genotyping is quite limited.…”
Section: Introductionmentioning
confidence: 99%
“…However, Campylobacter has recently been shown to have a high rate of carriage in cattle (Chatre et al, 2010), and the consumption of undercooked beef has been shown to be a significant risk factor for Campylobacter infection (Gallay et al, 2008). Typing of Campylobacter from different sources has shown clustering of isolates by host source Pittenger et al, 2009). However, a recent study of Irish C. jejuni isolates from poultry, beef and clinical sources has shown clinical isolates to cluster with isolates from both chicken and beef, highlighting the potential role for beef in the transmission of this pathogen to humans (Burgess et al, 2009). 10.4 Primary production 10.4.1 Pathogens in the farm environment When pathogens are shed in cattle faeces they can persist in the underlying soil and grass, surviving for extended periods ranging from several weeks to many months (Duffy, 2003;Semenov et al, 2009).…”
Section: Campylobacter Sppmentioning
confidence: 99%